2015
DOI: 10.1007/s11764-015-0443-1
|View full text |Cite
|
Sign up to set email alerts
|

A survivorship care plan for breast cancer survivors: extended results of a randomized clinical trial

Abstract: The transition of survivorship care from cancer center to the primary care setting showed no negative effect on health service and patient-reported outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 30 publications
4
86
0
1
Order By: Relevance
“…Yet that perceived lack of difficulty did not necessarily mean that patients received all aspects of recommended care. At 24 months' follow-up, Boekhout et al 47 found that 41% of control and 44% of intervention patients had received 3 or more clinical examinations, and that 68% of control and 69% of intervention patients had received 2 or more breast imaging tests. Guidelines for follow-up after breast cancer also include recommendations for psychosocial support, sexual functioning treatment, and other aspects of care 35,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Yet that perceived lack of difficulty did not necessarily mean that patients received all aspects of recommended care. At 24 months' follow-up, Boekhout et al 47 found that 41% of control and 44% of intervention patients had received 3 or more clinical examinations, and that 68% of control and 69% of intervention patients had received 2 or more breast imaging tests. Guidelines for follow-up after breast cancer also include recommendations for psychosocial support, sexual functioning treatment, and other aspects of care 35,48 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study of 408 early-stage breast cancer survivors randomized subjects to a survivorship care plan or a control group and reported no differences in cancerspecific distress, QOL, satisfaction, or health service outcomes [55]. Similarly, a systematic review of survivorship care plan outcomes reported that among 10 prospective studies of a variety of cancers, no significant benefit was found for distress, satisfaction, or coordination of cancer care [56].…”
Section: Survivorship Plansmentioning
confidence: 99%
“…The IOM also made key recommendations including the use of SCP’s to address many of the concerns raised by the current study’s participants [58]. There is a volume of literature suggesting that SCP’s may assist women to identify and address many of the ongoing issues and concerns relating to breast cancer survivorship [22, 25, 99, 133135]. …”
Section: Discussionmentioning
confidence: 99%